2021
DOI: 10.21203/rs.3.rs-946234/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing the Deep Root Growth and Water Uptake of Intermediate Wheatgrass (Kernza®) to Alfalfa.

Abstract: AimsWater is the most important yield-limiting factor worldwide and drought is predicted to increase in the future. Perennial crops with more extensive and deep root systems could access deep stored water and build resilience to water shortage. In the context of human nutrition, perennial grain crops are very interesting. However, it is still questionable whether they are effective in using subsoil water. We compared intermediate wheatgrass (Kernza®) Thinopyrum intermedium, a perennial grain crop, to alfalfa M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The first control was the option without fertilization. The second control was applying mineral fertilizers to sugar beet at balance-sheet doses (Molyuga, 2007;Schweinzer et al, 2017;Clement, 2021). The principle of calculating fertilizer doses was as follows: for the average yield over the years obtained by applying the recommended doses of fertilizer, the additional use of fertilizers determined the further increase of the crop.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first control was the option without fertilization. The second control was applying mineral fertilizers to sugar beet at balance-sheet doses (Molyuga, 2007;Schweinzer et al, 2017;Clement, 2021). The principle of calculating fertilizer doses was as follows: for the average yield over the years obtained by applying the recommended doses of fertilizer, the additional use of fertilizers determined the further increase of the crop.…”
Section: Methodsmentioning
confidence: 99%
“…Alfalfa, like other legumes, plays an important role in the organic processing of agriculture. Past findings revealed that every million hectares occupied by alfalfa enriched the soil with a vast amount of nitrogen, requiring several factories to produce the mineral nitrogen fertilizers (Fageria and Baligar, 2005;Schweinzer et al, 2017;Clement, 2021). It is critical for saving energy and economic costs for the production of nitrogen fertilizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guan et al (2016) indicated that SOC storage in the 0-200 cm soil layer increased by 14.6-24.1 Mg C ha À1 under the alfalfa, bush clover and milk vetch pastures over 7 years. Deep soil resources contributed substantially to the production and ecological functions of dryland ecological systems (Clément et al, 2022;Lynch & Wojciechowski, 2015). Yang et al (2020) and Lan et al (2021) all proved the positive effects of apple orchard on soil carbon storage to the depth of 1000 cm in the CLP.…”
mentioning
confidence: 93%